Growth patterns and e-moderating supports in asynchronous online discussions in an undergraduate blended course - Ghadirian, Hajar; Mohd Ayub, Ahmad Fauzi; Abu Bakar, Kamariah; Hassanzadeh, Maryam (Athabasca University Press, 2016)
This study presents a case study of asynchronous online discussions’ (AOD) growth patterns in an undergraduate blended course to address the gap in our current understanding of how threads are developed in peer-moderated AODs. Building on a taxonomy of thread pattern proposed by Chan, Hew and Cheung (2009), growth patterns of thirty-six forums were explored on three patterns: Short Thread Pattern (SHTP), Extended Thread Pattern (ETP), and Split Thread Pattern (STP). The impact of peer moderating supports on thread growth was also investigated. Types of peer moderators’ supports were explored utilizing a coding scheme from Smet, Keer, Wever, and Valcke’s (2010) study. STP pattern was found to be more common than the other patterns with 74 (37.94%) out of 195 threaded discussions growing on it. The results also showed that, compared to SHTP, in both STP and ETP the occurrences of ‘Information exchange’ and ‘Knowledge construction’ supports appeared to be more, while the presences of supports stimulating ‘Development’, ‘Access and motivation’ and ‘Socialization’ were less. Furthermore, the use of ‘Access and motivation’ and ‘Socialization’ supports appeared to enhance early thread termination when used individually. Thread continuity was reinforced by the use of ‘Knowledge construction’ support with other moderating supports.